Gaya Hidup dan Perilaku Konsumen terhadap Produk Fashion Lokal: Studi Kasus pada Saparo Store - Andrey Sheva Aditya Zebua; Tasya Syaqinah; Tifanny Az-zahra; Zainarti Zainarti (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to understand how lifestyle influences consumer behavior in choosing local fashion products, using Saparo Store as the case study. A qualitative approach was applied through in-depth interviews with customers who have purchased products from Saparo Store. The findings show that lifestyle plays an important role in purchasing decisions. Consumers tend to choose clothing that matches their character and daily activities. Saparo Store is perceived as suitable because it offers simple, comfortable, and attractive designs. Product quality, comfort, affordability, and a wide variety of styles also play significant roles in encouraging consumers to choose this brand. The study concludes that lifestyle, product quality, pricing, and product variety are the main factors influencing consumer decisions when buying local fashion products.